Pengelolaan kelompok dan implementasi teknologi pengolahan pakan ternak sapi potong di Kabupaten Bantaeng - Agustina Abdullah; Jamila Mustabi; Aslina Asnawi; Amidah Amrawati (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
There are districts Bantaeng Kalambaung cattle farmer groups engaged in development. Beef cattle development of the livestock industry beef cattle group are still simple with the feed forage. Available the community institutions be implement iptek devotion for the ( IbW ) relating to priority is the capacity to the problems of farmers and the utilization of technology in the development of beef cattle adoption of the technology still low. In addition , assess the potential this area as agricultural area rice and corn , so production waste rice and corn of abundant during harvest .The excavation and focus group discussions with farmers , information was obtained that rice straw and corn very abundant in during harvest time and not do the processing of feed rice straw and corn to be used as a source of animal feed at present dry season so as to feed not available a sustainable. He did not processing feed rice straw and corn because the farmers doesnt know and understand and consider also that rice straw and corn less popular by cattle. Activity program devotion IbW this with focuses on capacity building farmers by using all the potential here resources owned by the community to be a worth added , with introduce knowledge and technology owned by college with do technology transfer and assistance , implemented activities on the IbW is to do a variety of training and demonstration process technology straw for fodder .The results of products devotion the community difussion more wider at the community through products exhibition innovation in order cooperation with the local government of Bantaeng Regency. Activities received an enthusiastically by the community and regional government , with middle and teaching animal breeders to use the potential the region that is to become as fodder .The outcome of the activities it gave solution in solve the problems faced by farmers especially in the delivery of fodder chiefly beef cattle and goats.